New records of water mites (Acari, Hydrachnidia) from bromeliad phytotelmata in Brazilian Atlantic rainforest, with description of one new species - Pesic, Vladimir; Zawal, Andrzej; De Oliveira Piccoli, Gustavo Caue [UNESP]; Goncalves, Ana Zangirolame (Systematic & Applied Acarology Soc London, Natural History Museum, 2016)
New records of water mites (Acari, Hydrachnidia) from bromeliad phytotelmata in the Brazilian Atlantic rainforest are presented. One species, Protolimnesia goldschmidti (Limnesiidae) is described as new for science. It differs from all other species of the genus by the sixth segment of fourth legs having two subterminal setae extending beyond tip of segment. A first description of the female, deutonymph and larva is given for Xystonotus phytotelmaticola Pesic, (C) 2015 (Mideopsidae).
Keywords: water mites; new species; taxonomy; Brazil